Про структуру загального розв'язку та умови розв'язності задачі Коші для вироджених лінійних систем диференціальних рівнянь вищих порядків - Пафик, С.П.; Яковець, В.П. (Український математичний журнал, 2013)
Для системы линейных дифференциальных уравнений p-го порядка с тождественно вырожденной матрицей при старших производных найдены условия, при выполнении которых она имеет общее решение типа Коши. Определена структура этого решения. Установлены также условия существования и единственности решения соответствующей начальной задачи. For a system of linear differential equations of order p with identically degenerate coefficient matrix of higher derivatives, we establish conditions under which this system has the general solution of the Cauchy type. The structure of this solution is determined. Conditions for the existence and uniqueness of solution of the corresponding initial-value problem are also obtained.